2012
DOI: 10.1016/j.fishres.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and zoning compliance of recreational fishing in Ningaloo Marine Park, north-western Australia

Abstract: 1Recreational fishing is often permitted in multiple-use marine parks and, to ensure a 2 balance with biodiversity conservation, sanctuary (no-take) zones are frequently 3 demarcated. However, compliance with such measures is rarely quantified. Aerial and 4 land-based coastal observation surveys were conducted within Ningaloo Marine Park, 5 north-western Australia, with the aim of identifying the spatio-temporal distribution of 6 recreational fishing as well as quantifying participation and zoning compliance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 44 publications
3
49
0
Order By: Relevance
“…Educational programmes have been widely recommended to increase anglers' awareness of regulations (e.g. MLS), potentially shape moral attitudes and values, increase the release proportions of undersized fish, and promote better handling and release procedures (Raakjaer Nielsen and Mathiesen, 2003;Cooke and Suski, 2005;Edison et al, 2006;Lewin et al, 2006;Smallwood and Beckley, 2012;Veiga et al, 2013). One example of improved angling practice and the importance of correct angler education in C&R fisheries is the use of circle hooks.…”
Section: Potential For Improvements In Angler Educationmentioning
confidence: 99%
“…Educational programmes have been widely recommended to increase anglers' awareness of regulations (e.g. MLS), potentially shape moral attitudes and values, increase the release proportions of undersized fish, and promote better handling and release procedures (Raakjaer Nielsen and Mathiesen, 2003;Cooke and Suski, 2005;Edison et al, 2006;Lewin et al, 2006;Smallwood and Beckley, 2012;Veiga et al, 2013). One example of improved angling practice and the importance of correct angler education in C&R fisheries is the use of circle hooks.…”
Section: Potential For Improvements In Angler Educationmentioning
confidence: 99%
“…Smallwood and Beckley (2012) measured compliance in an Australian MPA using aerial and boat-based surveys. They found that aerial and coastal surveys yielded similar results; however, they identified 6.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, compliance levels reported by resource users and population density were the best predictors of reserve effectiveness in a study of 56 tropical marine reserves (Pollnac et al 2010). However, despite their importance for recovery, compliance rates are rarely quantified (Sethi and Hilborn 2008;Smallwood and Beckley 2012), and when compliance is measured, most data are qualitative (anecdotal or expert opinion) and direct empirical observations are rare (Bergseth et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snapper has a wide distribution across the western Indo-Pacific region (Smallwood et al, 2013). In the study region, it can exhibit spawning aggregations and the juveniles occupy sheltered coastal waters prior to migrating to deeper, more offshore waters (Smallwood et al, 2013). Baldchin groper is endemic to the southern west coast of Australia.…”
Section: Methodsmentioning
confidence: 99%